PENERAPAN MEDIA SOSIAL SEBAGAI SARANA KOMUNIKASI DAN PROMOSI EFEKTIF DI PT HAYYU PRATAMA DEALER - Dessi Nur Hidayah; Khairil Anwar (CV. ADIBA AISHA AMIRA, 2025)
The development of information and communication technology has changed marketing patterns and communication strategies for companies in various sectors, including the heavy equipment industry. This community service activity aims to analyse and optimise the use of social media as an effective communication and promotional tool at PT Hayyu Pratama Dealer, an official distributor of heavy equipment brands including Power Plus, Sunward, Liugong, Shacman, and UD Trucks. Through a participatory descriptive approach, this activity explores the company's digital communication practices, particularly the use of the TikTok platform as a promotional medium. The results of the activity show that social media is capable of increasing customer awareness and engagement, but still faces challenges in converting viewers into potential buyers (leads). The recommendations provided include increasing case study-based educational content, optimising B2B communication strategies, and digital marketing training for the company's internal team